Preferensi Pilihan Karir Mahasiswa sebagai Konten Kreator di Era Digital: Studi Kualitatif tentang Persepsi, Motivasi, dan Tantangan Mahasiswa Konten Kreator - Febri Ariyanti Kusuma Dewi; Nurul Fatimah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
The development of digital technology and social media has influenced students' career preferences. Content creators are becoming one of the most sought-after professions because they offer opportunities for creativity, personal branding, and potential income. This study aims to explore the factors (motivation, perception, and challenges faced) that influence students' preferences in choosing a career as content creators. Using a phenomenological qualitative approach, this study involved six active students in Semarang aged 18-25 years who had been content creators for six months to one year with at least 1,000 followers on social media. Data were collected through semi-structured purposive interviews and analyzed thematically. The results of the study show that the main motivation for students to become content creators comes from intrinsic factors (hobbies and the desire to channel creativity), while extrinsic factors (potential income and popularity) also play a role. Their perception of this profession is positive, seeing it as a means of self-expression, personal branding, not bound by office hours, allowing them to work from anywhere according to their personal rhythm, and adaptable to their studies or other activities. Supportive digital networks (connections) with flexible time and location requirements are also a major attraction. However, there are challenges such as time management, creativity demands, competition among content creators, and the psychological impact of negative criticism. Students are aware of these challenges, but still choose this profession based on rational considerations and benefits such as high flexibility, economic opportunities, and self-development that outweigh the risks. In line with James S. Coleman's rational choice theory, where students logically weigh the benefits (flexibility, creativity, income) against the disadvantages, content creation has become a strategic career in the digital age.